Clinical Outcomes and Risk Stratification of Early-Stage Melanoma Micrometastases From an International Multicenter Study: Implications for the Management of American Joint Committee on Cancer IIIA Disease. Issue 34 (1st December 2022) - Moncrieff, Marc D.; Lo, Serigne N.; Scolyer, Richard A.; Heaton, Martin J.; Nobes, Jenny P.; Snelling, Andrew P.; Carr, Michael J.; Nessim, Carolyn; Wade, Ryckie; Peach, A. Howard; Kisyova, Rumi; Mason, Jennifer; et al.
Abstract : PURPOSE: Indications for offering adjuvant systemic therapy for patients with early-stage melanomas with low disease burden sentinel node (SN) micrometastases, namely, American Joint Committee on Cancer (AJCC; eighth edition) stage IIIA disease, are presently controversial. The current study sought to identify high-risk SN-positive AJCC stage IIIA patients who are more likely to derive benefit from adjuvant systemic therapy. METHODS: Patients were recruited from an intercontinental (Australia/Europe/North America) consortium of nine high-volume cancer centers. All were adult patients with pathologic stage pT1b/pT2a primary cutaneous melanomas who underwent SN biopsy between 2005 and 2020. Patient data, primary tumor and SN characteristics, and survival outcomes were analyzed. RESULTS: Three thousand six hundred seven patients were included. The median follow-up was 34 months. Pairwise disease comparison demonstrated no significant survival difference between N1a and N2a subgroups. Survival analysis identified a SN tumor deposit maximum dimension of 0.3 mm as the optimal cut point for stratifying survival. Five-year disease-specific survival rates were 80.3% and 94.1% for patients with SN metastatic tumor deposits ≥ 0.3 mm and < 0.3 mm, respectively (hazard ratio, 1.26 [1.11 to 1.44]; P < .0001). Similar findings were seen for overall disease-free and distant metastasis-free survival. There were no survival differences between the AJCC IB patients and low-risk (< 0.3 mm) AJCC IIIA patients. The newly identified high-risk (≥ 0.3 mm) subgroup comprised 271 (66.4%) of the AJCC IIIA cohort, whereas only 142 (34.8%) patients had SN tumor deposits > 1 mm in maximum dimension. CONCLUSION: Patients with AJCC IIIA melanoma with SN tumor deposits ≥ 0.3 mm in maximum dimension are at higher risk of disease progression and may benefit from adjuvant systemic therapy or enrollment into a clinical trial. Patients with SN deposits < 0.3 mm in maximum dimension can be managed similar to their SN-negative, AJCC IB counterparts, thereby avoiding regular radiological surveillance and more intensive follow-up.